Pemanfaatan Platform Media Sosial sebagai Digital Marketing untuk Meningkatkan Penjualan Pelaku UMKM di Desa Paya Bili - Maulida, Intan; Aula, Rahmiatul; Febriansyah, Sutan; Rista, Lia; Mustika, Venna Maulida (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of this study is to analyze how social media platforms can be used as a digital marketing tool to increase sales for small and medium enterprises (MSMEs) in Paya Bili Village. With the development of digital technology, social media has become one of the most effective ways to promote products and reach a wider consumers, even in the retail sector. This research uses a qualitative approach with a case study methodology, where data is collected through interviews with MSME players, silent observation, and content analysis of social media platforms used by MSME players in the area. The research findings show that the use of social media platforms such as Facebook, Instagram, and WhatsApp can increase product visibility, increase sales, and streamline transactions. However, some limitations, such as limited availability of digital devices and internet access, are still an obstacle.